A Synthetic Population for Modelling the Dynamics of Infectious Disease Transmission in American Samoa. Issue 1 (December 2017) - Xu, Zhijing; Glass, Kathryn; Lau, Colleen; Geard, Nicholas; Graves, Patricia; Clements, Archie
Abstract Agent-based modelling is a useful approach for capturing heterogeneity in disease transmission. In this study, a synthetic population was developed for American Samoa using an iterative approach based on population census, questionnaire survey and land use data. The population will be used as the basis for a new agent-based model, intended specifically to fill the knowledge gaps about lymphatic filariasis transmission and elimination, but also to be readily adaptable to model other infectious diseases. The synthetic population was characterized by the statistically realistic population and household structure, and high-resolution geographic locations of households. The population was simulated over 40 years from 2010 to 2050. The simulated population was compared to estimates and projections of the U.S. Census Bureau. The results showed the total population would continuously decrease due to the observed large number of emigrants. Population ageing was observed, which was consistent with the latest two population censuses and the Bureau's projections. The sex ratios by age groups were analysed and indicated an increase in the proportion of males in age groups 0–14 and 15–64. The household size followed a Gaussian distribution with an average size of around 5.0 throughout the simulation, slightly less than the initial average size 5.6.